The Influence of Financial Leverage and Profitability on Tax Evasion: Company Size as A Moderation Variable - Wahyu; Suyanto (Jurnal AKSI (Akuntansi dan Sistem Informasi), 2024)
The study aims to determine the impact of financial leverage, profitability and the moderation effect of corporate size on tax evasion. The population of this study is the property and real estate sector companies listed on the Indonesian Stock Exchange for the period 2016-2022. There are 71 samples, selected using purposive sampling. The analysis in this study uses moderated regression analysis (MRA) to look at the influence of moderation of corporate size variables. Data collection through the official IDX website: www.idx.co.id. The results show that all the hypotheses built in this study are acceptable, that’s financial leverage and profitability have a positive and significant effect on tax evasion. Also, the moderation effect of corporate size has been shown to strengthen the influence on financial leverage and profitability against tax evasion.